Combining ability and reciprocal effects of earliness in native corn populations of Tamaulipas - Hernandez-Trejo, Antonia; López-Santillán, José Alberto; Estrada-Drouaillet, Benigno; Reséndiz-Ramírez, Zoila; Coronado-Blanco, Juana María; Malvar, Rosa Ana (Revista Mexicana de Ciencias Agrícolas, 2023)
The earliness and adaptation of native corn of Tamaulipas in restrictive environments allows considering it a source of variability for genetic improvement programs, so it is necessary to know the genetic effects that control its variation. The objective was to determine the gene action that controls the variation of the earliness of native corn populations of Tamaulipas and the relationship of earliness with grain yield. In Güémez, Tamaulipas, in the agricultural cycles of autumn-winter 2019-2020 and spring-summer 2020 with application and non-application of insecticide to combat S. frugiperda, the genetic effects of days to male and female flowering of six corn populations, their direct and reciprocal crosses were evaluated, through a diallel analysis with the Griffing method, the correlation between flowering and grain yield was analyzed. For male and female flowering, there were no effects of general combining ability and there were effects of specific combining ability, reciprocal and maternal: the variation between cultivars was explained in 53% for male flowering and 45% for female flowering by effects of specific combining ability, for male flowering 38% of the variation between cultivars and 43% for female flowering was due to reciprocal effects. The variation between cultivars depended on non-additive effects and there was cytoplasmic inheritance involved in their expression. Earliness was positively correlated with grain yield in the spring-summer cycle without insecticide application. With high specific combining ability, TML3S3×VHA and Cam×VHA stood out, to take advantage of the reciprocal effects in Cam×VHA, the order of the parents must be considered.